Mycobacterial Cell Wall Synthesis Inhibitors Cause Lethal ATP Burst - Shetty, Annanya; Dick, Thomas (Frontiers in Microbiology, 2018)
Mycobacterial cell wall inhibitors interfere with targets involved in synthesis of mycolic acids, arabinogalactan and peptidoglycan. These antibiotics corrupt structural integrity of the cell envelope and this is believed to be the cause of drug mediated cell death. Here, we show that treatment of Mycobacterium bovis BCG with these mechanistically different classes of cell wall inhibitors at MIC caused a 4 to 5-fold increase in intrabacterial ATP concentration. This effect on ATP homeostasis was specific to inhibitors of cell wall synthesis and not observed for other anti-tuberculosis drugs. Treating M. bovis BCG with sub-MIC concentrations of the ATP synthase inhibitor bedaquiline or the uncoupler carbonyl cyanide 3-chlorophenylhydrazone suppressed drug induced ATP surge, suggesting that the increase in ATP concentration was due to increased oxidative phosphorylation. Pharmacological suppression of the ATP burst attenuated bactericidal activity of the cell wall-targeting drugs up to 100-fold, suggesting that increased ATP levels are associated with the lethal effect of these antibiotics. Interestingly, inhibition of the ATP burst also suppressed induction of the promoter of the cell envelope stress response operon iniBAC by cell wall inhibitors suggesting a link between ATP surge and iniBAC expression. In conclusion, we show that treatment of M. bovis BCG with inhibitors of cell wall synthesis causes a burst of intrabacterial ATP by increasing oxidative phosphorylation. This ATP surge appears to be required for induction of the iniBAC cell envelope stress response operon and to contribute to drug induced cell death. Hence, this work revealed links between inhibition of cell wall synthesis, oxidative phosphorylation, iniBAC induction and cell death. The identification of the molecular mechanisms linking these processes may reveal novel targets for the discovery of bactericidal antibiotics.